Caractérisation Physico-Chimique Des Eaux De Surface Et Étude De La Diversité Ichtyologique De Quelques Zones Humides Continentales En Mauritanie - Tfeil, Hasni; Mahfoudh, Mohamed; Mhamed, Baba Aînina Moulay; Aliyen, Ahmed; Yarba, Lemhaba; Hmeyada, Abdellahi Mohamed Vall (European Scientific Journal, ESJ, 2018)
The aim of this study is to characterize the physicochemical parameters of the waters of certain continental wetlands and to determine the fish population diversity of this aquatic habitat in Mauritania. Physico-chemical analyses carried out in 2015-2016 (wet-fresh, hot-dry) suggest the qualities of good water, favorable to aquatic life at any time of the year. The highest values were recorded in the warm season (from 26.6 to 34.4 °C for the temperature, from 8 to 9.2 for the pH, from 170 to 591 μs/cm for the conductivity, from 3, 23 to 8.2 mg / l for dissolved oxygen and 169 to 590 mg / l TDS). The lowest values were found in the cold season (from 18.0 to 27.0 ° C for temperature, from 7.5 to 9.0 for pH, from 99.5 to 358 μs/cm for conductivity, 2.70 to 4.80 mg/l for dissolved oxygen and 100 to 360 mg/l of TDS). The establishment and development of biodiversity in these wetlands were at their peak during the hot and dry periods. 15 species belonging to 8 families were identified in these sites where there is a significant fishing activity. It is during this period that fish biodiversity and fishery potential increase as water decreases under the pressure of evaporation, infiltration and anthropozoogenic consumption. The ecosystem services of these continental wetlands, which survive the impacts of climate change, require urgent management, preservation and development measures.